Isolation, Identification, and Complete Genome Assembly of an Endophytic Bacillus velezensis YB-130, Potential Biocontrol Agent Against Fusarium graminearum - Xu, Wen; Zhang, Liyong; Goodwin, Paul H.; Xia, Mingcong; Zhang, Jie; Wang, Qi; Liang, Juan; Sun, Runhong; Wu, Chao; Yang, Lirong (Frontiers in Microbiology, 2020)
Wheat scab caused by F. graminearum is a highly destructive disease that leads to yield reduction and mycotoxin contamination of grains. In this study, an endophytic bacterium of strain YB-130 was isolated from surface sterilized wheat spikes with scab symptoms and identified as Bacillus velezensis by whole genome annotation, 16S rRNA gene and average nucleotide identities analysis. The whole-genome sequence of strain YB-130 was obtained by Pacbio sequencing. 88 putative Carbohydrate-Active Enzymes and 12 gene clusters encoding for secondary metabolites were identified in the YB-130 genome, including one gene cluster for the synthesis of lanthipeptide only found in strain YB-130 genome. In dual cultures, strain YB-130 significantly inhibited the growth of F. graminearum PH-1 and other eight fungal plant pathogens, indicating a broad antifungal activity. Furthermore, strain YB-130 was able to significantly inhibit spore morphology and hyphal development of F. graminearum PH-1. Strain YB-130 also reduced deoxynivalenol production by F. graminearum PH-1 in dual cultures, possibly due to its ability to suppress the expression of tri5, tri3 and tri8 that are required for deoxynivalenol production in F. graminearum. Overall, B. velezensis YB-130 is a promising biological control agent of both F. graminearum infection and mycotoxin production.